AN APPRAISAL OF NIGERIA’S FOREIGN POLICY THRUST FROM 1960-2023 - SUNNY MENE PIATE; EMMANUEL SUNDAY; BARILEDUM KIA (International Studies Journal)
The study appraised thematically (administration by administration) Nigeria’s foreign policy thrust since 1960 till 2023.  The justification for adopting this approach is to review how each Nigerian government undertook the conduct of Nigeria’s foreign policy and how it has translated to economic security and prosperity of the Nigerian State-cum-citizenry whose interest foreign policy is expected to serve.  The central proposition of the study is that for Nigeria’s foreign policy to be perceived as legitimate, its implementation must be seen by Nigerians to advance the domestic national development.  The study adopted three theoretical frameworks, the decision-making model, the power approach and the linkages theory in the analysis of the discourse.  The utility of the Decision-making model is that it seeks to uncover the underlying motivations and values that push decision makers towards preference a certain course of action.  The utility of the power approach to the discourse is that states in international relations are always possessed by the national interest which nations attain only by improving upon the element of their national power relative to other states.  The linkage theory emphasizes the interconnection between the domestic economy of any country and its foreign policy.  Findings from the study revealed that Nigeria allowed the system goals to take precedence over actor’s goals that would have reverberate in greater economic opportunity and prosperity for the people.  That this confusion over what constitutes Nigeria’s national interest and the procedure for its realization vividly explains why Nigeria’s foreign policy since independence until date has witnessed enormous cost without any corresponding dividends.  The study recommended, among other things, that Nigeria’s foreign policy thrust should be more inward focused, aimed at adding value to Nigeria’s development.